Outcomes of Craniofacial Open Surgery in Octogenarians - Ringel, Barak; Carmel-Neiderman, Narin N.; Ben-Ner, Daniel; Pery, Aviyah; Safadi, Ahmad; Abergel, Avraham; Margalit, Nevo; Fliss, Dan M. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Introduction The steady increase in average life expectancy has led to a rise in the number of referrals of elderly patients for major operations. It is not clear whether age itself is a risk factor for morbidity and mortality after skull base operations. We investigated a possible link among a cohort of patients older than 80 years of age who underwent those surgeries in our department.Methods We conducted a retrospective analysis of all patients who underwent skull base surgery at the TASMC (Tel Aviv Sourasky Medical Center) between 2000 and 2016.Results A total of 369 patients underwent open skull base surgeries in our institution, and 13 were patients older than 80 years. The median age of the octogenarians was 83.4 (range 80–89), and the male-to-female ratio was 7:6. Twelve patients had major systemic comorbidities. Four patients had major complications associated with surgery: three had early wound complications, and one each had early central nervous system complications, early and late systemic complications, and late orbital complications. This complication rate is comparable to that of our younger group of 356 patients. The overall survival rate was measured for 30 days, 1 year, and 3 years, and it was not significantly different between the octogenarians and that of the younger patients. Further comparison of the elderly group with 13 matched younger patients revealed no difference of morbidity and mortality between the two groups.Conclusions Despite their systemic comorbidities, the morbidity and mortality rates associated with skull base surgery in octogenarians appear to be comparable to that of younger patients undergoing the same procedures.
Keywords: skull base surgery; octogenarians; complications; elderly